Pengembangan Sentra Bibit Aren Sebagai Upaya Keberlanjutan Usahatani Aren di Desa Langke Gorontalo Utara - Hasan, Fardyansjah; Sudiarta, I Made; Anas, Muhammad; Taan, Hapsawati; Hasanuddin, Hasanuddin; Dako, Amirudin (PPPM POLTESA, 2024)
Sugar palm is a plant that is difficult to cultivate, so farmers generally only expect it to grow naturally. This has resulted in the population of sugar palm trees decreasing due to the lack of activities to expand the population of sugar palm plants. The purpose of this community service activity is to develop farmers' interest in cultivating sugar palm, then develop the location of the sugar palm nursery center in Langke Village. The methods used in this activity include observation activities, then socialization and training, then conducting field practice. The results of the activity, namely the creation of a sugar palm seedling development center carried out in Langke Village, are an important step in developing farmers' awareness of the existence of sugar palm trees. Furthermore, from this activity, the positive value obtained is that farmers' knowledge increases and becomes a pioneer for further development by farmers independently. The shortcomings faced in this activity are that the availability of materials such as polybags and manure still have to be taken from Gorontalo City, which is about 80 km from Langke Village. The next development is the practical activity of making planting holes and determining the location for planting sugar palm.